2007
DOI: 10.1007/s10765-007-0210-2
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Formation of Thin Films by Photothermal Technique

Abstract: Evaporation is a widely used technique for developing thin films. In this study the formation of a film on top of a substrate is investigated using a photothermal technique. The configuration implies the illumination of an opaque substrate by modulated laser radiation and the detection of the heat at the illuminated zone. The system is considered as a two-layer system in which the non-illuminated layer presents a dynamic response, the thickness and thermophysical properties, which change as a function of time.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…For the second stage, after 500 s, a characteristic minimum appears when the thermal diffusion length of the sample is comparable with the thickness of the sample. This behavior has been predicted theoretically, and its interpretation has to do with the interference of thermal waves [8]. In the last stage, the PA signal increases, strongly reaching a final constant value that corresponds to the end of the process of the film formation.…”
Section: Resultssupporting
confidence: 53%
See 3 more Smart Citations
“…For the second stage, after 500 s, a characteristic minimum appears when the thermal diffusion length of the sample is comparable with the thickness of the sample. This behavior has been predicted theoretically, and its interpretation has to do with the interference of thermal waves [8]. In the last stage, the PA signal increases, strongly reaching a final constant value that corresponds to the end of the process of the film formation.…”
Section: Resultssupporting
confidence: 53%
“…The time evolution of a similar system to the one analyzed here has been studied theoretically [8]. It has been shown that the main characteristics of the curves can be understood considering a simple two-layer system as shown in Fig.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…PAs have been used recently in the study of the evolution of dynamic systems, such as oxygen release in plants, blood sedimentation, evaporation of liquids, etc. [8][9][10][11]. The PA signal is not only directly related to the time evolution of the optical and thermal properties, but also with various physical processes leading to modulated heat and additional changes in the geometry of the sample [12].…”
Section: Introductionmentioning
confidence: 99%